2019
DOI: 10.1101/765016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sequences of Intonation Units form a ~1 Hz rhythm

Abstract: 10

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Besides the low ecological validity of such stimuli, they further rely on the assumption that speech and music share similar cognitive time constants. However, speech unfolds faster than music (Ding et al, 2017), and while a linguistic phrase typically lasts less than a second (Inbar et al, 2020), a melodic phrase is an order of magnitude longer. Moreover, balancing the complexity/simplicity of linguistic and musical stimuli can be challenging, and musical stimuli are often reduced to very simple melodies played on a synthesizer.…”
Section: P R E P R I N T 1 Introductionmentioning
confidence: 99%
“…Besides the low ecological validity of such stimuli, they further rely on the assumption that speech and music share similar cognitive time constants. However, speech unfolds faster than music (Ding et al, 2017), and while a linguistic phrase typically lasts less than a second (Inbar et al, 2020), a melodic phrase is an order of magnitude longer. Moreover, balancing the complexity/simplicity of linguistic and musical stimuli can be challenging, and musical stimuli are often reduced to very simple melodies played on a synthesizer.…”
Section: P R E P R I N T 1 Introductionmentioning
confidence: 99%
“…We found that sequences of IUs form a ∼1 Hz rhythm in all these languages, despite substantial variation in their grammatical structures and socio-cultural profiles. The consistent temporal structure of IUs across languages provides further evidence for their importance in cognition (Inbar et al, 2020).…”
Section: Introductionmentioning
confidence: 94%
“…Based on our previous work demonstrating that sequences of IUs form ∼1 Hz rhythms (Inbar et al, 2020), we hypothesized that from a continuous perspective, the time course of responses to IUs would give rise to delta-band neural speech tracking. We use the estimated responses from the GLM model to predict the continuous EEG response to our stimuli and perform a neural speech tracking analysis on the empirical EEG and on the model-predicted EEG (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Neural speech tracking has become an increasingly useful tool for studying how the brain encodes and processes continuous speech (Obleser and Kayser, 2019; Brodbeck and Simon, 2020). Importantly, characterizing linguistic attributes of speech on a continuous basis gives a new angle to auditory attention and neurolinguistics, as researchers have been able to dissociate neural responses driven by the acoustics of speech from those capturing higher-order processes in a dynamically changing speech signal (Brodbeck et al, 2018; Keitel et al, 2018; Inbar et al, 2020; Gillis et al, 2021). And yet, the speech stimuli used in these studies are generally highly scripted and edited, taken – for example – from audiobooks or TED talks, which are also extensively rehearsed and are delivered by professionals.…”
Section: Introductionmentioning
confidence: 99%